Description of Sleep Quality in Diabetes Mellitus Patients at Pisangan Health Center (HEALTH CARE: JURNAL KESEHATAN, 2025)
Background: Diabetes Mellitus (DM) is one of the non-communicable diseases that is widely suffered by the Indonesian population. Poor sleep quality is often experienced by DM patients due to symptoms such as nighttime urination or extremity pain. Purpose: This study aims to describe the sleep quality of diabetes mellitus patients at Puskesmas Pisangan. Methods: The research method used is descriptive quantitative with a cross-sectional approach. This study involved 50 respondents selected using purposive sampling technique. The instrument used to measure sleep quality is the PSQI (The Pittsburgh Sleep Quality Index) questionnaire. Results: The results based on characteristics showed that poor sleep quality was found in respondents aged 56-65 years (88%), both females and males (80%), and those who had been suffering from DM for less than 5 years (84%). The conclusion of this study is that the sleep quality of diabetes mellitus patients at Puskesmas Pisangan is generally poor. More optimal intervention efforts are needed in diabetes mellitus management to improve the sleep quality of DM patients.